2021
DOI: 10.1155/2021/2210191
|View full text |Cite|
|
Sign up to set email alerts
|

Study on the Application and Efficacy of Responsibility Nursing in Dialysis Care

Abstract: Providing high-quality care to patients undergoing hemodialysis (HD) is a priority for nurses. The present study was conducted to explore the experiences of the quality of nursing care among patients, nurses, and caregivers in Yanghu Branch of Changzhou Second People’s Hospital, China. A total of 120 hemodialysis patients consecutively admitted to Yanghu Branch of Changzhou Second People’s Hospital were enrolled and divided into two groups according to the nursing method they received: control group (routine n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%